Maritirukan Aku Bisa: Android application for learning social skills of children with social emotional barriers - S. Suharsiwi; Rd. Heri Solehudin; Erna Budiarti; Noor Azura Zakaria; Siti Rohmah (Research and Development in Education (RaDEn), 2024)
Android application development for online knowledge dissemination is urgently needed at this time. This study aims to develop an android application for learning social skills of children with social emotional barriers. The research participants consisted of 10 students, 75 respondents including teachers and parents of students in partner schools from Jakarta, Purwokerto, Pekanbaru, and Banjarmasin. The design of the android application was validated by four educational experts from universities. Data were collected through questionnaires and FGDs, and analyzed descriptively. The results obtained are the android application model "Maritirukan Aku Bisa with interactive features developed in the form of films, games, movements and songs as well as recording media of student activities, themes developed from aspects of social skills such as attention/concentration, expression/emotions, effective communication, and independence. The android application "Maritirukan Aku Bisa" with updates developed in this study is in accordance with the needs of parents and teachers. The material provided is in accordance with the needs and characteristics of children with social-emotional barriers, and can be accessed independently with the assistance of parents at home. This answers the needs of parents, especially in remote areas throughout Indonesia.